The certainty of uncertainty : dialogues introducing constructivism - Pörksen, Bernhard (Imprint Academic, 2004)
"This book presents the views of the founders of constructivism and modern systems theory, who are still providing cues for international scientific debate. The conversations display a kind of thinking that steers clear of rigid fixation and reveals the ideal of objectivity to be a myth. The conversations turn on the results of brain research, the breaks through of cybernetics, the linguistic determination of thought, and the intrinsic connection between epistemology and ethical practice." "Throughout, the central figure of the observer is examined. Constructivism thus emerges as a philosophy of possibilities that keeps generating new points of view, insists on fundamental scepticism with regard to certainties and dogmas, and provides the foundation for an ethics of perception: Each and every one of us is responsible for their view of things."--Jacket